1975
DOI: 10.1152/jn.1975.38.4.780
|View full text |Cite
|
Sign up to set email alerts
|

Unit activity in posterior association cortex of cat

Abstract: 1. "Association" neurons in the posterior middle suprasylvian gyrus of cat were found to be predominantly polysensory, with 82% of the units in the chloralose-anesthetized preparation responding to auditory, visual, and somatic stimuli. There was no evidence of response differentiation associated with cortical depth distribution. Most units responded with a short-latency response (median 35-60 ms) to all stimulus modalities, with the response to visual stimulation occurring at the shortest latency. Among polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…We found a mean rate in all three cortical areas of 10 spikes/s, which is considerably higher than that reported by yon Griinau et al (1987) in PMLS, Camarda and Rizzolatti (1976), and Blakemore and Zumbroich (1987). Robertson et al (1975) also found the same trend: a mean spontaneous rate of 0.6 spikes/s in chloralose-anesthetized cats and 14.6 spikes/s in unanesthetized cats. However, our result is not higher than mean rates found in PLLS by von Griinau et al (1987), though the shapes of the histograms are quite different: our distribution is nearly exponential (Fig.…”
Section: Comparisons With Anesthetized Catssupporting
confidence: 62%
See 1 more Smart Citation
“…We found a mean rate in all three cortical areas of 10 spikes/s, which is considerably higher than that reported by yon Griinau et al (1987) in PMLS, Camarda and Rizzolatti (1976), and Blakemore and Zumbroich (1987). Robertson et al (1975) also found the same trend: a mean spontaneous rate of 0.6 spikes/s in chloralose-anesthetized cats and 14.6 spikes/s in unanesthetized cats. However, our result is not higher than mean rates found in PLLS by von Griinau et al (1987), though the shapes of the histograms are quite different: our distribution is nearly exponential (Fig.…”
Section: Comparisons With Anesthetized Catssupporting
confidence: 62%
“…By contrast, there are no systematic studies of the MS area in awake cats and only a few reports in anesthetized animals. The early studies of this area showed that under anesthesia many cells respond to moving visual stimuli and some are multimodal (Dow and Dubner 1969;Robertson et at. 1975) while in awake cats some cells discharge in synchrony with saccadic eye movements (Straschill and Schick 1974;Joseph and Giroud 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, investigations of auditory responses outside acknowledged regions of auditory cortex took place in association areas regarded at that time as ‘polysensory.’ Many of these initial forays took place in the cat, and regions of the anterior suprasylvian gyrus, middle suprasylvian gyrus and anterior ectosylvian gyrus were identified as showing evoked or single-unit responses to somatosensory, visual and/or auditory stimulation (e.g., see Albe-Fessard and Fessard, 1963; Thompson et al, 1963; Schneider and Davis, 1974; Robertson et al, 1975). Similar approaches were used to identify polysensory areas in non-human primates, such as the superior temporal sulcus and prefrontal areas (e.g., see Nelson and Bignall, 1973; Benevento et al, 1977; Hikosaka et al, 1988) or, in rodents, the parietotemporal cortices (e.g., see Di et al, 1994; Brett-Green et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the cat, these cortical areas are primarily located within the middle suprasylvian gyrus (MSg) or cytoarchitectonically in areas 5 and 7 (Gurewitsch and Chachaturian, 1928). Neurons located in this region were originally described as polysensory (Amassian, 1954); although later studies indicated that neurons within this region could be categorized primarily based on their responses to visual stimuli, including stationary spots, brisk movements, and oriented edges (Thompson et al, 1963; Dubner, 1969, 1971;Robertson et al, 1975; Yin and Greenwood, 1992a,b). More recently, visual, saccade, and fixational responses were distinguished within more caudal portions of the MSg (Yin and Greenwood, 1992b).…”
mentioning
confidence: 99%